How Capital Structure and GCG (Good Corporate Governance) Shape Firm Value: Evidence from Property Firms) - Aisyah, Siti; Purwanto, Agus (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This study investigates the influence of capital structure, profitability, and good corporate governance on firm value in the Indonesian property, real estate, and construction sectors. The research aims to provide empirical evidence on how financing decisions, financial performance, and governance mechanisms affect firm value in a post-pandemic period when the sector faces significant challenges. The study used purposive sampling to select 57 firms listed on the Indonesia Stock Exchange during 2021–2023. Multiple linear regression analysis was applied to examine the relationship between the variables. The findings reveal that capital structure, measured by the debt-to-equity ratio, has a significant positive effect on firm value, while profitability, measured by return on assets, does not influence firm value. In contrast, the presence of independent commissioners as a proxy for good corporate governance significantly enhances firm value. Compared to previous studies, the results show a divergence in the role of profitability, suggesting that investor valuation is not always aligned with accounting performance indicators. The study highlights the importance of governance structures and optimal financing decisions in maintaining firm value during periods of economic uncertainty. The research concludes that future studies should incorporate additional variables such as firm size or dividend policy and apply more advanced analytical methods to provide deeper insights.